ANALISIS PENGGUNAAN RUDAL X-22 DALAM PERANG RUSIA- UKRAINA MENURUT HUKUM HUMANITER INTERNASIONAL - Muhammad Michael Kahfi; Arlina Permanasari (Fakultas Hukum Universitas Trisakti, 2022)
In the Russo-Ukrainian conflict, two X-22 long-range missiles fired by Russian troops from a Tu-22M3 bomber from the Shaykovka airfield in the Russian territory of Kaluga and destroyed shopping center in the city of Kremenchuck, Central Ukraine, 27 June 2022. The incident killed at least 13 people and injured 50 local residents. This paper discusses the lagality of using means and methods of warfare in the framework of the basic rules on the means and methods of war under international humanitarian law. This research is normative research with a qualitative content analysis approach. The analysis was carried out based on several humanitarian law instruments, namely the basic rules stipulated in Article 22-23 of the Hague Regulations 1907, Article 35 and Parti II – IV of Additional Protocol I of 1977. It was concluded that the X-22 missile is a conventional weapon that can be used in an armed conflict but the methods or use must still comply with the basic rules on the means and methods of warfare, the principle of distinction and other humanitarian law principles.